KISAH KEHIDUPAN SYEIKH ABDUL QADIR AL-JAILANI - Salih Ahmad Al-Syami, author 316902; Faizah Othman, translator 549055 (Selangor : AL HIDAYAH HOUSE OF PUBLISHERS SDN. BHD., 2011)
Noreha binti Mat Isa @ Abdul Rahman;